The asthenosphere of Ukraine according to geoelectric studies - Burakhovych, T.K.; Ilienko, V.A.; Kushnir, A.M.; Stolpakov, A.Y.; Tonkovyd, E.M.; Bondar, A.M. (Geofizicheskiy Zhurnal, 2025)
For the first time, a model-scheme of the geoelectric asthenosphere was created, the parameters of were obtained by generalizing the models built based on experimental electromagnetic data. The parameters of three «normal» sections of ρn for geological regions of Ukraine of different ages are confirmed. High electrical conductivity anomalies in the upper mantle have a complex configuration, different intensity and depth, and do not always correspond to the geology. The asthenosphere in the southwestern megablocks, local areas of the Ingul megablock of the Ukrainian shield, as well as the southern part of the Volyn-Podilsky Plate is picked fragmentarily from 50―70 to 120―160 km with anomalous resistivity of 20―50 Ohm·m. Local objects in the Pripyat-Dnipro-Donetsk Depression have similar parameters. The Scythian Plate has anomalous areas: crustal mantle (30―40 to 60 km deep with a resistivity of 10 Ohm·m) and upper mantle (60―90 km deep with a resistivity of 100 Ohm·m). In the Carpathian region, the asthenosphere is heterogeneous, probably consisting of regions that differ in resistivity and may branch with depth. A general deepening of its upper boundary to the northeast from 40 to 90―100 km has been confirmed.